2021
DOI: 10.3390/diagnostics11111969
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis and mtDNA Haplogroup Characterization in Three Serbian Cases of Mitochondrial Encephalomyopathies and Literature Review

Abstract: Mitochondrial encephalomyopathies (MEMP) are heterogeneous multisystem disorders frequently associated with mitochondrial DNA (mtDNA) mutations. Clinical presentation varies considerably in age of onset, course, and severity up to death in early childhood. In this study, we performed molecular genetic analysis for mtDNA pathogenic mutation detection in Serbian children, preliminary diagnosed clinically, biochemically and by brain imaging for mitochondrial encephalomyopathies disorders. Sanger sequencing analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 114 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…We can first screen for hot spot gene mutations in Chinese MELAS syndrome patients such as mtDNA3243A>G, mtDNA13513G>A and mtDNA3271T>C, or perform full-length mtDNA sequencing and/or related nuclear gene detection[ 13 ]. The mutated gene in most patients with MELAS syndrome is mtDNA3243A>G[ 2 , 5 ]. The region where the mtDNA3243A locus is located encodes a transfer RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can first screen for hot spot gene mutations in Chinese MELAS syndrome patients such as mtDNA3243A>G, mtDNA13513G>A and mtDNA3271T>C, or perform full-length mtDNA sequencing and/or related nuclear gene detection[ 13 ]. The mutated gene in most patients with MELAS syndrome is mtDNA3243A>G[ 2 , 5 ]. The region where the mtDNA3243A locus is located encodes a transfer RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial encephalomyopathy (ME) is a multisystem metabolic disorder mainly caused by mutations in mitochondrial DNA (mtDNA) or nuclear DNA, resulting in abnormal mitochondrial structure and function and insufficient ATP synthesis[ 1 , 2 ]. ME has six main subtypes: ME, lactic acidosis, and stroke-like episode (MELAS) syndrome; Leigh syndrome (LS); Leber’s hereditary optic neuropathy; chronic progressive external ophthalmoplegia (CPEO); myoclonus epilepsy with ragged-red fiber (MERRF); and Keams-sayre syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, modifications of tRNA caused by mutations are linked to numerous mitochondrial and neurological diseases [ 37 , 51 ]. By literature searching, we also noticed that m.12308A>G of tRNA Leu(CUN) had been reported to be associated with mitochondrial encephalomyopathies [ 52 ] and syndromes of Wolfram and chronic progressive external ophthalmoplegia [ 53 ]. It was also reported to be associated with increased ROS production and considered a risk factor for many diseases such as severe knee osteoarthritis [ 54 ], stroke [ 55 ], breast cancer [ 56 ] and AD in men [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, m.12372G>A was found in patients with LHON [ 60 ], a maternally inherited mitochondrial blinding disorder caused by mtDNA mutations and known to be associated with MS [ 13 ]. Moreover, both variants were reported in Creutzfeldt–Jakob disease, a degenerative brain disorder [ 61 ] and in patients with mitochondrial encephalomyopathies [ 52 ]. In addition, previous studies have identified some of the functional effects of these two variants.…”
Section: Discussionmentioning
confidence: 99%